PENYALAHGUNAAN KEWENANGAN OLEH PEJABAT PEMERINTAH DALAM PASAL 10 AYAT (1) HURUF E UNDANG-UNDANG NOMOR 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN - Resti Khairunnisa Fitri; Dian Pertiwi; Saadatul Maghfira; Dodon Alfiander (Institut Agama Islam Negeri Batusangkar, 2023)
: This study examines the abuse of authority committed by Government Officials, in this case the Head of the Tanah Datar Regency Koperindag Office for the 2019 Period. This research is a Library Research research. The researchers' secondary data sources are taken from Law Number 30 of 2014 concerning Government Administration and books related to research. The results of the research obtained by the author are that the former Head of the Koperindag Office of Tanah Datar Regency for the 2019 period allegedly violated Article 10 Paragraph (1) Letter e of Law Number 30 of 2014 because he had abused his authority in this case based on the source of attribution authority regarding a bribery case with a contractor of the X Koto market construction project, Tanah Datar Regency. According to Siyasah Dusturiyah, Government Officials fall within the scope of Wizarah Tanfidz. Islam forbids any abuse of authority by Government Officials because Allah forbids bribers and bribes in legal matters